Relationship between Abdominal Circumference and Incidence of Hypotension during Cesarean Section under Spinal Anesthesia - Pattaraleeya Thomard; Sunthiti Morakul; Nichawan Wirachpisit; Wichai Ittichaikulthol; Chawika Pisitsak (Anesthesiology Research and Practice)
Background. Enlarged uterus can compress the inferior vena cava and cause hypotension when lying supine. Previous studies have shown a positive association between the abdominal circumference and size of the uterus. Therefore, the aim of this study was to evaluate the relationship between abdominal circumference and incidence of hypotension during cesarean section under spinal anesthesia. Methods. The study cohort comprised women undergoing cesarean section under spinal anesthesia. Patients were divided into two groups according to the median abdominal circumference (<101 cm and ≥101 cm). Hypotension was defined as a systolic blood pressure of <90 mmHg or mean arterial pressure of <65 mmHg. The primary outcome of this study was the relationship between the incidence of hypotension and the abdominal circumference after spinal anesthesia in term pregnant women. Results. The study cohort comprised 100 women. The incidence of hypotension did not differ between the groups (71.42% in the smaller vs. 78.43% in the larger abdominal circumference group, p=0.419). However, the decrease in mean arterial pressure and its percentage decrease from baseline were greater in the larger than in the smaller abdominal circumference group (change in mean arterial pressure: 28.33 mmHg (18.66–33.67) in the smaller vs. 36.67 mmHg (23.34–43.34) in the larger abdominal circumference group, p=0.004; percentage decrease: 31.41% (22.74–39.22) in the smaller vs. 38.47% (28.00–44.81) in the larger abdominal circumference group, p=0.022). Conclusions. Large abdominal circumference in pregnancy is associated with greater decreases in mean arterial pressure from baseline. However, the incidence of hypotension defined by standard criteria did not differ between larger and smaller abdominal circumference groups.